Wideband linearly or circularly polarized monopulse tracking corrugated horn. - Biao Du
A design of a wideband monopulse tracking corrugated horn, for either a linearly or a circularly polarized signal, is presented. Two types of suppressors are introduced to restrain the excitation of unwanted higher order modes. Parametric dependence curves of special points on the propagation characteristics are given for m=1 and m=2 modes in the ring-loaded corrugated horn. By using the suppressor and employing ring-loaded slots in the entire horn, the cross-polarization peak level of the horn can be reduced by a further 10 dB or more in the transmitting band, and its maximum level is less than -28 dB across C-band. The experimental results of return loss and sum and difference patterns validate that the feed possesses satisfactory wide-band communication and tracking characteristics
Keywords: 3.625 to 4.2 GHz; 5.85 to 6.425 GHz; C-band.; Antenna feed; Circularly polarized antenna; Cross-polarization level; Higher order mode suppression; Linearly polarized antenna; Monopulse tracking antenna; Radiation patterns; Return loss; Ring-loaded corrugated horn antenna; Satellite communication earth station antennas; Shipborne antennas; Wideband antenna